2022
DOI: 10.3389/fbioe.2021.798496
|View full text |Cite
|
Sign up to set email alerts
|

Hip–Knee Coupling Exoskeleton With Offset Theory for Walking Assistance

Abstract: To alleviate the influence of aging on the elderly, a hip–knee coupling exoskeleton with offset theory is designed in this article to improve people’s athletic ability. With the novel design, the unique application strategy of the offset principle for hip and knee joints is developed, and a hip–knee coupling mechanism is proposed to solve the discrete power assistance problem for the knee joint. To acquire the success of the design, the mathematical model of the coupling mechanism is established to optimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Due to the lack of objective comparative conditions among all existing exoskeletons, the effect of the cooperativity model on the exoskeleton was indicated by comparing the walking-assistance efficiencies of the exoskeletons with the same structure but with different elastic parameters of the energy storage components. The dynamic simulations showed that there exists and only one set of elastic parameters that can be set to obtain the maximum value of the walking-assistance efficiency, which is in line with the judgment of references [ 3 , 25 ] and the maximum values were 17.95% and 18.51% respectively for the hip joint and knee joint, which are generally higher than the previous lower-limb-assistant exoskeleton [ 3 , 4 , 23 , 24 , 30 , 31 ]. In addition, to actual test the walking-assistance efficiency of the exoskeleton with the optimal parameter combinations, the respiratory metabolisms with and without the exoskeleton were compared to calculate the efficiency, in which there is a regularity between the changes of the metabolic gases [ 22 , 24 , 33 ], and the exoskeleton provided the average walking-assistance efficiency of 14.45% for more than 80% of the subjects, which slightly higher than the previous-exoskeleton tests [ 22 , 24 , 33 ].…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Due to the lack of objective comparative conditions among all existing exoskeletons, the effect of the cooperativity model on the exoskeleton was indicated by comparing the walking-assistance efficiencies of the exoskeletons with the same structure but with different elastic parameters of the energy storage components. The dynamic simulations showed that there exists and only one set of elastic parameters that can be set to obtain the maximum value of the walking-assistance efficiency, which is in line with the judgment of references [ 3 , 25 ] and the maximum values were 17.95% and 18.51% respectively for the hip joint and knee joint, which are generally higher than the previous lower-limb-assistant exoskeleton [ 3 , 4 , 23 , 24 , 30 , 31 ]. In addition, to actual test the walking-assistance efficiency of the exoskeleton with the optimal parameter combinations, the respiratory metabolisms with and without the exoskeleton were compared to calculate the efficiency, in which there is a regularity between the changes of the metabolic gases [ 22 , 24 , 33 ], and the exoskeleton provided the average walking-assistance efficiency of 14.45% for more than 80% of the subjects, which slightly higher than the previous-exoskeleton tests [ 22 , 24 , 33 ].…”
Section: Discussionsupporting
confidence: 79%
“…The calculation results of each curve are shown in Figure 13 , and the walking-assistance efficiencies were 5.41%, 9.02%, 16.88%, 18.51%, and 16.72%, respectively, in which the KESM with the optimal parameter combinations exhibited the highest walking-assistance efficiency [ 3 , 25 ]. The walking-assistance efficiencies of simulation are generally higher than the previous lower-limb-assistant exoskeleton [ 3 , 4 , 23 , 24 , 30 , 31 ] but far less than the theoretical limit of walking-assistance, which is 66.72%.…”
Section: Verification and Discussion On The Function Of The Cooperati...mentioning
confidence: 71%
See 3 more Smart Citations